Detecting bacterial endophytes in tropical grasses of the Brachiaria genus and determining their role in improving plant growth - Kelemu, Segenet; Fory Sánchez, Paola Andrea; Zuleta, C; Ricaurte, Jaumer; Rao, Idupulapati M.; Lascano Aguilar, Carlos Eduardo (Academic Journals, 2011)
Plant-growth-promoting (PGP) bacteria include a diverse group of soil bacteria thought to stimulate plant growth by various mechanisms. Brachiaria forage grasses, of African origin, are perennials that often grow under low-input conditions and are likely to harbour unique populations of PGP bacteria. Three bacterial strains that tested positive for nitrogenase reductase gene sequences (nifH) were isolated from Brachiaria hybrid CIAT 36062 and introduced into Brachiaria hybrid cv. Mulato, which also had indigenous endophytic bacteria testing positive for nifH gene sequences. Under conditions of nutrient deficiency, inoculated Mulato plants had significantly higher biomass production, chlorophyll and total nitrogen contents in leaves than do control plants and were darker green. Strains of endophytic bacteria were then artificially introduced into Brachiaria brizantha CIAT 6294, which does not have indigenous endophytic bacteria. Results were consistent with those obtained with artificially inoculated Mulato plants, suggesting that these endophytic bacteria do benefit plant growth. DNA sequence analysis demonstrated that the nifH gene sequences were highly similar to those from Klebsiella pneumoniae and other N2?fixing organisms and that the nif genes had consensus sequences identical to those of other N2-fixing bacteria.